A Literature Review: The Use of Artificial Intelligence (AI) In Mathematics Learning - Nurwahid, Mohammad; Ashar, Sofia (Proceeding International Conference on Religion, Science and Education, 2024)
Artificial Intelligence (AI) has brought about major changes in education, including in the teaching and learning of mathematics. This article discusses the use of AI in learning mathematics. The research conducted included descriptive research with a qualitative approach. The method used in this research is Systematic Literature Review (SLR). This research was conducted by identifying, reviewing related articles and evaluating articles according to the theme and then interpreting them. Model analysis uses the Miles model through three steps, namely data collection, verification, and drawing conclusions. The results of the study show that the use of AI in mathematics learning includes: personalizing learning, making automatic assessments and proofreaders, virtual tutors, and game-based interactive learning.